Leadership Strategy of the Head of the UPTD Siwa Lima Museum in Provinces of Maluku in Improving Employee Performance - Fientje, Palijama; Batjo, Sitti N (Garuda Prestasi Nusantara Consulting, 2024)
This research aims to understand and analyze leadership strategies and employee performance at the UPTD Siwa Lima Museum office, Maluku Province. The informants in this research were 5 respondents. The analytical method used in this research is a qualitative descriptive approach. The research results show that the leadership strategy at the Siwa Lima Ambon Museum has a very negative effect on employee performance. This happens because of a weak leadership strategy. This is evidenced by the lack of involvement of employees in the socialization of the Vision and Mission so that employees do not understand the purpose of the vision and mission, the human resources used are not in accordance with needs, employees are not optimal in participating in training activities and employees are less disciplined when entering and leaving the office and are not even optimal in carrying out Assigned job